A Quick Method to Assess Site Quality of Young Chir Pine Stands - Gupta, B.; Sahu, R. K. (Indian Forester, 2015)
In the present study a quick method termed as 'Height Intercept Method' is used to determine site quality of any chir pine forests/stands. The study was conducted in Solan district of Himachal Pradesh (India) selecting eight chir pine sites viz., Oachghat, Sultanpur, Barog, Shilli, Bauhli, Kandaghat, Subathu and Dharampur) Height and Height Intercepts i.e. 3, 4, 5, 6 and 7th year mean internodal length for 19 years old trees were measured from breast height. Relationships between mean internodal lengths (height intercept) and height of trees were developed using linear, curvilinear, log linear and log curvilinear models. The results revealed that 6 years height intercept was reliable estimate to express the relationship between height of tree and height intercept of 19 years old chir pine stands and thereby the site quality. The best relationship between height and height intercept was: Height = 3.0493 + 0.1419 Height Intercept + 0.0007 Height Intercept2 . Height intercept varied from 30 to 70 cm. Chir pine in Dharampur site exhibited lowest height intercept thus expressing poor site quality whereas, chir pine in Oachghat was maximum height intercept thereby good site quality. The site quality as estimated by height intercept method were compared with standard site qualities given by Forest Research Institute of India (F.R.I.) for chir pine stands/forests and it was found that good site quality of present study was equivalent to site quality I/II and poor site quality equaled site quality III of F.R.I.